ANTIPROLIFERATIVE EFFECT ON BREAST CANCER (MCF7) OF Moringa oleifera SEED EXTRACTS - Adebayo, Ismail Abiola; Arsad, Hasni; Samian, Mohd Razip (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: Moringa oleifera belongs to plant family, Moringaceae and popularly called ―wonderful tree‖, for it is used traditionally to cure many diseases including cancer in Africa and Asia, however, there is limited knowledge on cytotoxic activity of Moringa oleifera seeds on MCF7 breast cancer cell. The present study evaluated antiproliferative effect on MCF7 of the seed. Materials and Methods: Seeds of Moringa oleifera were grinded to powder and its phytochemicals were extracted using water and 80% ethanol solvents, part of the ethanolic extract were sequentially partitioned to fractions with four solvents (hexane, dichloromethane, chloroform, and n-butanol). Antiproliferative effects on MCF7 of the samples were determined. Finally, potent samples that significantly inhibited MCF7 growth were tested on MCF 10A. Results: Crude water extract, hexane and dichloromethane fractions of the seeds inhibited the proliferation of MCF7 with the following IC50 values 280 μg/ml, 130 μg/ml and 26 μg/ml respectively, however, of the 3 samples, only hexane fraction had minimal cytotoxic effect on MCF 10A (IC50 > 400μg/ml). Conclusion: Moringa oleifera seed has antiproliferative effect on MCF7.